Indução da ovulação em éguas crioulas com diferentes doses de gonadotropina coriônica humana - Beal, Jordana (2008)
The effect of three different i.v. doses of human chorionic gonadotropin (hCG), as far as the possible influence of aging, follicular diameter and the month of the breeding season (September to January), was evaluated for ovulation induction in one hundred and twenty three Criollo mares, between 2 and 24 years old, during the 2006 breeding season. The mares were examined daily by rectal palpation and ultrasonography with a 5MHz linear transrectal transducer. When the ovarian follicles reached a diameter of 30 to 35mm, ovulation was induced with an injection of hCG. Mares were assigned into three groups, each one receiving a different i.v. dose of hCG (1000 IU; n=39, 1500 IU; n=41, 2000 IU; n=43). Mares were bred in the next day and examined daily until ovulation was detected. Percentage of mares ovulating before 24h of pharmacology induction was 10.5%, 7.3% e 4.7%, and before 48h, 92.5%, 83.7% and 86.0%, respectively, for groups of 1000, 1500 and 2000 IU of hCG. The month of the breeding season, age of the mares or follicular diameter (30-35mm) had no influence on ovulation response. The injection of hCG showed similar (P>0.05) effects with the tree doses studied. Ovulation was induced, until 48h after injection when a pre-ovulatory follicle 30- 35mm in diameter was visualized. Criollo mares with 30 to 35mm diameter pre-ovulatory follicles can have their ovulation induced when treated with 1000 UI, 1500 UI or 2000 UI of hCG.